USING MODIFIED GAMEJEOPARDY! AND HOP-SCOTCH TO IMPROVE ENGLISH VOCABULARY MASTERY OF SEVENTH GRADERS IN SMP NEGERI 1 BONDOWOSO (RETAIN, 2014)
USING MODIFIED GAMEJEOPARDY! AND HOP-SCOTCH TO IMPROVE ENGLISH VOCABULARY MASTERY OF SEVENTH GRADERS IN SMP NEGERI 1 BONDOWOSO Yuniar Bestiana English Department, Languages and Arts Faculty, State University of Surabaya ybestiana_196@yahoo.co.id Prof. Dr. Hj. Lies Amin Lestari, M.A., M.Pd English Department, Languages and Arts Faculty, State University of Surabaya lies.aminlestari@yahoo.com Abstrak Kosakata adalah aspek utama dan mendasar (dari sebuah bahasa) yang harus dikuasai penuturnya. Oleh karena itu, pembelajaran kosakata yang tepat akan mengoptimalkan hasil belajar siswa dalam belajar bahasa. Berdasarkan pengamatan awal yang dilakukan, pembelajaran kosakata membuat siswa menjadi bosan dan akhirnya, siswa tidak dapat memperoleh hasil yang maksimal. Untuk itu, penggunaan media dalam bentuk permainan bahasa dipercaya efektif untuk menciptakan sebuah pembelajaran kosakata yang dapat membantu kesuksesan hasil belajar siswa (Huyen dan Nga, 2003). Penelitian ini menggunakan metode dua grup eksperimental dengan pretest danposttest untuk mengetahui efektivitas penggunaan permainan modifikasi Jeopardy! dan engklekdalam meningkatkan hasil belajar pembelajaran kosakata bahasa Inggris di kelas VII SMP Negeri 1 Bondowoso. Kuesioner digunakan untuk mengetahui respon siswa setelah diajar menggunakan permainan tersebut. Hasil analisis uji t menjelaskan bahwa siswa di kelas eksperimental mendapatkan hasil yang lebih tinggi secara statistik dibandingkan dengan siswa di kelas kontrol, dengan nilai t 3.6, nilai p .001 (df=66), dan eta squared .16. Ini menunjukkan bahwa penggunaan permainan modifikasi Jeopardy! dan engklek secara statistik dapat meningkatkan kemampuan siswa dalam mempelajari kosakata. Data dari kuesioner juga menunjukkan bahwa lebih dari 80% siswa menyukai permainan ini dan setuju bahwa permainan yang digunakan telah memenuhi 5 kriteria desain permainan oleh Hill, et. al (2013). Kata Kunci: kosakata, Jeopardy!, engklek, kelas VII Abstract Vocabulary becomes the first and the foremost aspect of a language which should be mastered by every language learner. That is why; a good vocabulary instruction will result in the success of learning achievement. Preliminary observation done showed that the existing vocabulary teaching made students feel demotivated and thus they could not achieve a satisfying result. Thus, the use of media in the form of language game is believed to create a more motivating instruction which leads students to be a successful learner (Huyen & Nga, 2003). Using a two-group pretest and posttest experimental design, this study aimed to explore the effectiveness of using modified game Jeopardy! and Hop-scotch to teach vocabulary in reading descriptive text about things around to the seventh graders in SMP Negeri 1 Bondowoso and investigate the response of the students after being taught by using the game. Using independent samples t-test analysis, the scores of posttest of the two groups were compared and the result showed that by using the game, students in the experimental group scored significantly higher than students in the control group, with the t value of 3.6 and p value of .001 (df = 66, mean difference = 11.2), eta squared of .16. This shows that the modifiedgame Jeopardy! and Hop-scotch was effective to improve students’ vocabulary mastery. Furthermore, data from the questionnaire which was analyzed by using descriptive statistics showed that more than 80% of the students gave positive responses and agreed that the game fulfilled the five criteria of game design proposed by Hill, et.al(2013). Keywords:Vocabulary, Jeopardy!, Hop-scotch, Seventh graders INTRODUCTION If the ability to use a certain language can be analogized to a car, vocabulary is the fuel. Without having enough fuel, the car will not work. Vocabulary is an important element which constructs a language and it can be used to show the degree of mastery of the speakers or students (Schmitt, Schmitt, & Chaplam, 2001). Experts agree that developing vocabulary, both theoretically and practically, is very essential in the language learning process in which students at every level should focus on strengthening their vocabulary because it can determine the success of learning. Students are still able to communicate without the correct form of grammar; but not without vocabulary because without syntax or grammar, students can still maintain the meaning; but without vocabulary, students cannot find the meaning of certain word or sentence (Folse, 2003). In addition, most students are having difficulty to say what they want to say because of their insufficient vocabulary (Chastain, 1988). It can be said that vocabulary is the key to be a successful language speaker. In teaching vocabulary, the teacher nowadays uses drillings and other repeated written exercises to enable the students memorize the vocabulary. He gives the students a certain text and asks them to find the synonym, antonym, or the meaning of a word which is stated in the text. The students find that this kind of teaching activity is not enjoyable, yet de-motivating (Hill, Sumarniningsih, & Lestari, 2013). Moreover, the teaching-learning processes are mostly teacher-centered, where the teacher talks all over the time, explains the material and the students sit and listen to the teacher (Huyen & Nga, 2003). As a result, students are very passive during the teaching and learning process. As regard to the explanation above, it can be inferred that the on-going teaching and learning process could not give the students positive experience since the way the teacher conduct the instruction is likely to be de-motivating and teacher-centered. Thus, the teacher as a director and facilitator of learning experiences should find a solution for this problem; the teacher should create an instructional design which enables students to acquire the language effectively as well as gives the students positive experience (Bortoluzzi, 2003). Therefore, applying instructional media in the classroom may be a key to manage the poor condition since instructional media can set up conditions in which the students acquire knowledge, skill, and attitudes more easily. There are numerous kinds of instructional media which can be used in teaching and learning process. Hence, the teacher should choose one among those kinds of media which is the most suitable for the teaching-learning process, the condition of the students and school, and the availability and practicality of the media (Gerlach & Ely, 1980). Experts have classified the various instructional media into several categories. The most common classification is made based on its form; whether it is visual, things that can be seen; audio, things that can be heard; audiovisual, things that can be both seen and heard; or multimedia, things that combine all form of media and mostly uses computer. So far, the use of multimedia is being a trend in teaching. The use of multimedia has been broadly used by the teacher due to the fact that most of people nowadays, especially school-aged children and teenagers, are very familiar with the use of technology. Moreover, it is believed that the use of multimedia technology can change the old classroom setting which tends to be teacher-centered and de-motivating to become a sophisticated classroom setting which engage and give positive experience to the students during the teaching-learning process (Abdelraheem & Rabame, 2005). One of the implementation of multimedia is the use of computer game. Game is used as a media based on the consideration that game can engage the students in an enjoyable and challenging activity so that the students can actually practice the language (Shaptoshvili, 2002). They will concentrate on how they win without having to be worry whether they use the correct structure or pattern of the language. But still, soon or later, their fluency and accuracy in using the language will be increased, thus they can attain the communicative competence. Game also provides the students the knowledge of language in a meaningful context of a language (Chen & I-Jung, 2005). By engaging in a game-context activity, students give good responses and show their positive attitude (Uberman, 1998). Furthermore, a result of an action research confirm the effectiveness of the game since students likely to need relatively short period to learn and attain the materials in an enjoyable and comfortable environment than those activities in traditional classes (Huyen & Nga, 2003). One of the games which can be used in vocabulary teaching is Jeopardy!, which is actually an American quiz television show, a quiz in which the participants choose one question with a certain score and will achieve the score if they are success or lose the score if they are failed answering the question (